Evaluating fear of crime in neighbourhood: a structural equation approach / Siti Rasidah Md Sakip ... [et al.] - Md Sakip, Siti Rashidah; Abdullah, Aldrin; Johari, Noraini; Mohd Salleh, Mohd Najib (Universiti Teknologi MARA, Perak, 2011)
Fear of crime is based on three preferences which are crime-specific, crime problems in neighbourhood and environmental factors such as physical disorder, social disorder and victimization. Most findings by the researcher found that those dimensions show a high level of reliability to measure the fear of crime. Therefore, in this paper the dimensions of fear of crime were tested using confinnatory factor analysis with a series of measurement model. The validation and confirmation of the fear of crime construct was done using Confirmatory Factor Analysis (CF A) via AMOS. Nineteen items were initially involved in measuring the three categories of fear of crime dimensions, but six items were excluded from the list of variable indicators of the fear of crime dimensions because these items have a factor loading below 0.3. The results of this study indicate that the crime problems in neighbourhood (CPN) and environmental factors (EF) dimensions achieved good fit indices where the values for GFI, TU and CFI exceeded 0.90 and the RMSEA value was less than 0.05.